The Social capital and corruption puzzle : evidence from a Palestinian survey - Andriani, Luca; Palestine Economic Policy Research Institute (Ramallah Palestine Economic Policy Research Institute (MAS), 2011)
Palestinian perceptions about corruption and tax evasion can be affected by their endowment of social capital. This paper tries to estimate the probabilities that Palestinians will claim to be more against corruption in the presence of high social capital. This estimation is based on binomial logit regression models, where indicators of corruption are the dependent variables and the proxies of social capital are included in the group of explanatory factors. The empirical analysis uses a unique data set derived from the "Survey on Social capital" conducted by the Palestine Economic Policy Research Institute (MAS) in 2007. The survey contains several sections where a number of opinions regarding civic spirit, trust, shared values, norms and corruption have been collected from a random sample of individuals (2,350 observations) in West Bank and Gaza Strip. The indicators of corruption consist of the perceptions that Palestinians have concerning the importance of fighting corruption, the use of bribes at work and tax evasion. Empirical evidence indicates that the probability of claiming to be against the use of bribe and tax evasion is higher for individuals that trust institutions and people in general, but lower for individuals more involved in associational activities. Moreover, we find that individuals that consider the rule of law very important are likely to declare that the use of bribes at work and tax evasion cannot be justifiable at all.
1. Introduction -- 2. Social Capital and Corruption: Literature Review and Measures -- 3. The Corruption in the Palestinian Context -- 4. Data Description and Variables -- 5. Methodology and Empirical Analysis -- 6. Conclusions and Policy Recommendations -- References
Title page and introduction and and executive summary also in Arabic
Bibliography : p. 31-34
Keywords: Social problems and services; CORRUPTION; Social Capital; PALESTINE